2007
DOI: 10.1007/s10545-007-0462-9
|View full text |Cite
|
Sign up to set email alerts
|

Peak bone mass in patients with phenylketonuria

Abstract: Peak bone mass is decreased in PKU patients. Possible explanations include long-standing dietary deficiency in protein, calcium, vitamin D or trace elements, or a primary defect in bone turnover inherent to the disease itself. Our data do not favour any of these hypotheses. Further studies are needed to elucidate the cause of low bone density in PKU patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
2
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 41 publications
(55 reference statements)
8
79
2
9
Order By: Relevance
“…Previous assessments of bone mineral density in PKU have been performed almost exclusively by DXA (5)(6)(7)(8)(9). A single study by using peripheral computed tomography revealed a prominent impairment of trabecular bone compartment, with only minor changes of cortical bone (44).…”
Section: Discussionmentioning
confidence: 99%
“…Previous assessments of bone mineral density in PKU have been performed almost exclusively by DXA (5)(6)(7)(8)(9). A single study by using peripheral computed tomography revealed a prominent impairment of trabecular bone compartment, with only minor changes of cortical bone (44).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also find no correlations between dietary calcium, protein, and energy intake and BMD, BMD Z-score or BTM in patients of any age (Carson et al 1990;McMurry et al 1992;Hillman et al 1996;Modan-Moses et al 2007;Lage et al 2010). Positive correlations have been reported, however, between total calcium and phosphorus intake and BMD Z-score (PerezDuenas et al 2002) and calcium and protein from medical food and spine BMD (Geiger et al 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Since the first report in 1962 of abnormal bone structure in neonates and infants with phenylketonuria, low BMD has been described in male and female patients of all age groups (Feinberg and Fisch 1962). Though inconsistent criteria have been used to define low BMD, osteopenia, and osteoporosis, low BMD may be present in nearly 50% of individuals with PAH deficiency (Modan-Moses et al 2007). The most recent meta-analysis, however, suggests a much lower prevalence of low BMD of 10% (Demirdas et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A -1 és -2,5 közötti Z-score prevalenciája phenylketonuriában nemzetközi adatok szerint 28-46%-os, míg -2,5 alatti Z-score 5-14% körüli gyakorisággal fordul elő [1,8,22]. A nemzetközi közlemények alapján a betegek körülbelül 10%-a rendelkezik -2 alatti, vagyis a kronoló-giaihoz képest alacsony csontsűrűséggel [1].…”
Section: Megbeszélésunclassified
“…A tö-rési kockázatot mindössze egyetlen kutatás vizsgálta, mely 2,6-szeres kockázatnövekedést talált az egészséges kontrollcsoporthoz képest [6]. Azonban a felnőtt PKUsok csontháztartására vonatkozó nemzetközi irodalom egyelőre elenyésző, ezen közlemények is sokszor egymásnak ellentmondó eredményeket ismertetnek [7][8][9]. Szintén nem egyértelmű ma még az orvosi tápszerek és a csontsűrűség (BMD) közötti kapcsolat [10,11].…”
unclassified